Soft Computing and Medical Bioinformatics - Muppalaneni, Naresh Babu; Ma, Maode; Gurumoorthy, Sasikumar (SpringerBriefs in Forensic and Medical Bioinformatics, 2019)
This book highlights the applications of soft computing techniques in medical bioinformatics. It reflects the state-of-the-art research in soft computing and bioinformatics, including theory, algorithms, numerical simulations, and error and uncertainty analysis. It also deals with novel applications of new processing techniques in computer science. This book is useful to both students and researchers from computer science and engineering fields.